The two halves of U-shaped mortality - Levitis, Daniel A.; Martínez, Daniel E. (Frontiers in Genetics, 2013)
Gerontology focuses on deterioration with increasing age, but in most populations most variables, including survival probability, improve at early ages (ontogenescence) before deteriorating at advanced ages (senescence). The extent to which gerontology needs to consider this U-shaped pattern of risk over age depends upon the mechanistic, demographic and evolutionary links and interactions between ontogenescence and senescence. In reading the literature on both senescence and ontogenescence, and in interacting with other biogerontologists, we have encountered a set of what we view as inaccurate or oversimplified claims about ontogenescence, its relationship to senescence and its importance to gerontology. Here, after briefly introducing ontogenescence, we address four of these claims. We demonstrate the counterfactual nature of Claim 1. Ontogenescence is an environmental effect largely absent in protected environments. We then briefly review the literature which leads to Claim 2. Senescence and ontogenescence are parts of the same phenomenon, and describe why we reject this view. We then explain why the rejection of Claim 2 does not necessarily support Claim 3, the idea that senescence and ontogenescence are easily separable. Finally, we examine Claim 4. Gerontologists don’t need to think about ontogenescence, and give some examples of why we consider this misguided.